Effect of pectin polysaccharides on formation of productivity and bioenergetic efficiency of cultivation of table carrot - S. V. Kokovkina (Аграрная наука Евро-Северо-Востока)
Influence of pectin polysaccharidess on the seed sowing properties, growth and development of carrot plants is studied in the conditions of Republic of Komi. As a growth bio-stimulants water solutions of some pectins are used in experiments: lemnan - extracted from a small duckweed (Lemna minor L.); silenen - from callus tissue of campion (Silene vulgaris (M.) G. [Oberna behen (L.) Ikonn]); heracleuman - from Sosnovsky hogweed (Heracleum sosnowsky L.). It is established that at seed treat with preparations energy of germination increased by 9.9-15.5% and laboratory germination by 10.5-12.0%. Infection with pathogenic fungi Alternaria radicina M.Dr. et E in seeds treated with bio-stimulants lowed down from 11.8 in control to 0.3% in a variant with silenen. Sowing material under influence of preparations was fully disinfected from the causative agent of bacteriosis Erwinia carotovora (Jones) Holl. It assisted the acceleration of carrot shoots' appearance by 3-4 days; the increase in vegetative mass of plants; and an earlier onset of beam maturity. Treatment of seed and sowing of carrot substantially influenced on the increase of mass of root crops. By the time of technical maturity root mass under the influence of pectin polysaccharides increased by 11.0-28.9% compared with the control. As a result, the overall yield increased respectively by 14.5-30.7%. The most energy effective variant of treatment is selected - use of pectin polysaccharides from campion tissue which obtained productivity of table carrot of 39.6 t/ha at less energy cost of a 1 ton of products (by 5.6%) in comparison with control.